Solutions of clinical guideline implementation in Iran: A qualitative study - Mina Azizzadeh; Javad Babaie; Ali Janati; Sakineh Hajebrahimi (Journal of Education and Health Promotion)
BACKGROUND: Despite all of the positive effects that are considered for clinical guidelines, according to studies, it has been determined that there is a gap between the development of clinical guidelines and their implementation. This study was conducted to explore the practical solutions to smooth the way of implementing clinical guidelines in this country through interviews with experts. MATERIALS AND METHODS: This descriptive qualitative study was conducted between January 2023 and October 2023. Data were collected through focused group discussions (FGDs) and semi-structured interviews. A purposive sampling method was used. The participants included specialist doctors, faculty members, employees, policymakers, and managers. Data collection continued until data saturation. The data of this study were analyzed by the qualitative content analysis method. Four criteria of validity, verifiability, trustworthiness, stability, and transferability were used for the reliability. RESULTS: The implementation solutions were classified into five main strategy categories, including providing necessary infrastructures, improving the development process of clinical guidelines, reforming the educational system of doctors and paramedics, providing a suitable implementation context, and creating a mechanism to follow up the implementation of guidelines. CONCLUSION: The implementation of clinical guidelines in Iran should be paid attention to the form of a continuous process. Therefore, policymakers must have a process perspective. It is important to note that in addition to the need to provide the necessary infrastructure; this process begins with the development of clinical guidelines and continues with steps, such as the need for a proper educational system, proper implementation, and appropriate supervision.